High genetic diversity vs. low genetic and morphological differentiation of Argiope trifasciata (Araneae, Araneidae) in Tunisia. Issue 1 (2nd January 2017) - Dimassi, Najet; Khadra, Yousra Ben; Othmen, Abdelwaheb Ben; Ezzine, Issaad Kawther; Said, Khaled
Abstract : We examined morphological and genetic variation within and among populations of the spider Argiope trifasciata (Forsskål, 1775) in Tunisia. One hundred and twenty-five spiders were collected from 13 localities spread over three climatic subdivisions. Analyses of sequence variation in a 631bp segment of the mitochondrial cytochrome oxidase c subunit I ( cox1 ) gene revealed low nucleotide diversity but high genetic diversity within populations ( Hd = 0.729). A noticeable genetic differentiation was found in all populations. However, no genetic differentiation was observed within climatic subdivisions. Sixteen haplotypes were identified. Connectivity between populations, except for the Gabes population, was relatively high, which could be explained by the high dispersal ability of these spiders by passive aerial movement through the wind (ballooning). Our results indicate that gene flow between Gabes and the remaining regions was limited. In corroboration with the genetic data, morphological analyses did not show differentiation among populations or according to climatic subdivisions. Demographic stability of A. trifasciata populations mediated by gene flow was observed. Moreover, a homogeneous phenotypic trend was observed within A. trifasciata populations across Tunisia. This finding could be explained by the high conservation of external morphological characters within the spider lineages, which are therefore not affected by environmental factors.